First report of Anisakis sp. (Nematoda: Anisakidae) parasitizing Muscovy duck in Marajó Island, state of Pará, Brazil - Elaine Lopes de Carvalho; Ricardo Luis Sousa Santana; Evonnildo Costa Gonçalves; Raul Henrique da Silva Pinheiro; Elane Guerreiro Giese (Revista Brasileira de Parasitologia Veterinária)
Abstract Among the avian used for human consumption, the Muscovy duck is well adapted to various climatic conditions and its breeding is widespread due to its easy handling, and its meat is widely consumed and appreciated, especially in the cuisine of northern Brazil. The present study aimed to report and identify taxonomically the nematodes found in the esophagus of Muscovy ducks reared and marketed in the municipality of Soure, Marajó Island, state of Pará, Brazil, and discuss its zoonotic potential to human. The samples consisted of 30 specimens of Cairina moschata domestica analyzed. A total of 258 nematodes were recovered, which were strongly fixed in the esophageal mucosa of hosts. The morphological and morphometric characteristics were compatible with Anisakis third-stage larvae.